Glycobiology of Eosinophilic Inflammation: Contributions of Siglecs, Glycans, and Other Glycan-Binding Proteins - O’Sullivan, Jeremy A.; Carroll, Daniela J.; Bochner, Bruce S. (Frontiers in Medicine, 2017)
The historical focus on protein-protein interactions in biological systems, at the expense of attention given to interactions between other classes of molecules, has overlooked important and clinically relevant processes and points of potential clinical intervention. For example, the significance of protein-carbohydrate interactions, especially in the regulation of immune responses, has recently received greater recognition and appreciation. This review discusses several ways by which cell surface lectin-glycan interactions can modulate eosinophil function, particularly at the levels of eosinophil recruitment and survival, and how such interactions can be exploited therapeutically. A primary focus is on discoveries concerning Siglec-8, a glycan-binding protein selectively expressed on human eosinophils, and its closest functional paralog in the mouse, Siglec-F. Recent advances in the synthesis of polymeric ligands, the identification of physiological ligands of Siglec-8 and Siglec-F in the airway, and the determination of the basis of glycan ligand discrimination of Siglec-8 are discussed. Important similarities and differences between these siglecs are outlined. Eosinophil expression of additional glycan-binding proteins or their glycan ligands, including interactions involving members of the selectin, galectin, and siglec families, is summarized. The roles of these molecules in eosinophil recruitment, survival, and inflammation are examined. Finally, the modulation of these interactions and potential therapeutic exploitation of glycan-binding proteins and their ligands to ameliorate eosinophil-associated diseases are considered.